Making Strategy Work: An Organizational Ethnography - Marie Mathiesen (Copenhagen Business School (CBS), 2013)
This PhD thesis is an ethnographic exploration of strategy work in practice. The academic contribution of the thesis is positioned in the overlap between Critical Approaches to Strategy and Strategy as Practice. This implies a critical position that does not take strategy for granted and which emphasizes a philosophical understanding of the practice concept. Other studies have adopted a similar Critical Strategy as Practice position, but very few ethnographic studies of strategy work have been conducted from this point of departure. Thus, the thesis aims to contribute two-fold to the existing Critical Strategy as Practice literature: One, to strengthen the tradition theoretically through the development and mobilization of a conceptual braid of practice, narrative, and performativity; and two, to provide an extensive empirical analysis of strategy work from this perspective. The case for the thesis is strategy work in the Stakeholder Department of a multinational biotech corporation, which is here called Bioforte. The thesis explores the dual aspects of the title as “making strategy-work”—the specific doings of crafting strategy; and “making Strategy work”—finding ways for strategy, as a concept, to function in the context of an organization. Building on the double entendre of the title, the guiding research question for this exploration is quite simply: What does strategy work do? The answer to this question is, however, not simple, because as the ethnographic exploration demonstrates, strategy work in the Stakeholder Engagement Department at Bioforte has a range of performative effects. Through narratives of everyday practice, the thesis demonstrates how strategy work contributes to organizing the organization by shaping The Strategy Working Group, the department, the work, and the selves of the people working with strategy. The organizing force of strategy work is partly achieved through the continual collective creation and maintenance of distinctions such as strategic/operational and left brain/right brain. In this sense, the thesis argues that the organizing forces of strategy is to be found in the performative nature of strategy work.
hdl:10398/8663
Keywords: 650